Neighborhood Socioeconomic Status and Health Care Costs: A Population-Wide Study in the Netherlands - de Boer, Willem I. J. (Am J Public Health, 2019)
Objectives. To identify disparities in several types of insured health care costs in the Netherlands across neighborhoods with different socioeconomic statuses and to assess the room for improvement. Methods. We used 2015 Dutch whole-population registry data to estimate the age- and gender-specific cost structure by neighborhood for total, specialist, pharmaceutical, and mental health care. Classifying neighborhoods by the quintile of their neighborhood socioeconomic status (NSES), we determined differences in observed and expected health care costs for several scenarios of NSES improvement. Results. From low to high NSES, we found a clear downward gradient in health care costs. Total health care costs would drop by 7.3% if each neighborhood’s cost structure was equal to that of the most affluent neighborhoods. The potential for cost reduction appeared highest for females, for age groups between 40 and 60 years, and for pharmaceutical care. Conclusions. Low NSES is associated with relatively high health care costs, and represents considerable potential for cost savings in health care. Public Health Implications. Our research suggests that policies aimed at improving the socioeconomic determinants of health locally may be pivotal in containing health care costs.